Adaptive Communication, Ostracism, and Psychological Safety - I Putu Yoga Purnama Wijaya; Komang Widhya Sedana Putra P (INJECT (Interdisciplinary Journal of Communication), 2026)
Contemporary workplaces are increasingly characterized by complex interpersonal dynamics that expose employees to subtle forms of social risk in everyday interactions. Within human resource management research, psychological safety has been widely recognized as a critical condition for employee voice, learning, and performance. However, existing studies have largely emphasized leadership and structural determinants, with limited attention to how individual adaptive behavior operates within ongoing communication processes. This study addresses this gap by conceptualizing social chameleon behavior as an adaptive communication strategy used by employees to navigate workplace interactions, while positioning workplace ostracism as a mediating mechanism linking individual behavior to psychological safety. Using a quantitative approach, data were collected through a structured survey and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that adaptive behavior does not exert a direct effect on psychological safety. However, it significantly reduces workplace ostracism, which in turn has a strong negative impact on psychological safety. These results suggest that the influence of individual adaptability operates indirectly through informal dynamics of inclusion and exclusion. By integrating perspectives from organizational communication and human resource management, this study highlights the role of interaction processes in shaping psychological safety and offers practical insights for developing more inclusive and supportive workplace environments.